Oxidation of Maleic Acid by Tetraethylammonium Chlorochromate in an Aquo-Acetic Acid Medium- A Kinetic and Mechanistic Study - Awasthi, Anupam; Tomer, Ashish; Singh, J.V. (Asian Journal of Chemistry, 2010)
The oxidation of maleic acid by tetraethylammonium chlorochromate (TEACC) was studied, in the presence of perchloric acid and in acetic acid-water mixtures (50 % v/v). The reaction is first order with respect to maleic acid, tetraethylammonium chlorochromate and acid. Ionic strength changes have no significant effect on the reactivity. The reaction does not induce polymerization of acrylonitrile. The reaction rates were determined at different temperatures and the activation parameters were computed. The reaction rate increased with increasing amount of acetic acid in the mixture. A suitable mechanism consistent with the observed kinetic results has been proposed.